2014
DOI: 10.1109/surv.2013.081313.00218
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Symbol Joint Signal Processing for Differentially Encoded Single- and Multi-Carrier Communications: Principles, Designs and Applications

Abstract: Abstract-Bypassing the potentially excessive-complexity and yet inaccurate channel estimation, differentially encoded modulation in conjunction with low-complexity non-coherent detection constitutes a viable candidate for future multiple-antenna aided systems, where estimating all the links may become unrealistic, especially in high-speed environments. Upon exploiting the correlation between the phase distortions experienced by the consecutively transmitted symbols and/or based on mutually and iteratively util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…should compare the proposed scheme to the family of stateof-the-art training-based channel estimation schemes [50][51][52] or the S-DSTC scheme designed for time-varying channels [22,23,35,[53][54][55]. All the existing studies have indicated that the coherent counterpart of a non-coherent scheme having perfect channel state information (PCSI) can be regarded as a performance upper-bound.…”
Section: Performance Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…should compare the proposed scheme to the family of stateof-the-art training-based channel estimation schemes [50][51][52] or the S-DSTC scheme designed for time-varying channels [22,23,35,[53][54][55]. All the existing studies have indicated that the coherent counterpart of a non-coherent scheme having perfect channel state information (PCSI) can be regarded as a performance upper-bound.…”
Section: Performance Resultsmentioning
confidence: 99%
“…Different from Fig. 8, we considered the normalized Doppler frequencies of F d T s = 10 −3 and 10 −2 [55]. As shown in Fig.…”
Section: B Frequency-selective Wideband Scenariomentioning
confidence: 99%
“…Figure 2 depicts the bit-error-rate (BER) performances of various QOSTBC systems as a function of signal-to-noise (SNR), when E sr =r n;R ¼ 20 dB. It is firstly observed that the DC-QOSTBC systems outperform the DD-QOSTBC systems, of which result can be expected from a traditional communication system [3]. It is found that the DD-QOSTBC (P1) systems outperform the DD-QOSTBC (P3) systems as SNR increases because Protocol I provides additional information during Time-slot 1.…”
Section: Performance Evaluationsmentioning
confidence: 98%
“…In particular, the advantages of MIMO systems, such as capacity and diversity improvements are compared with singleinput single-output (SISO) system adopting the combination of the differential modulation and an orthogonal space time block code (STBC) [3][4][5]. Unfortunately, however, employing a large number of antennas has been considered as an impractical direction for small mobile terminals due to its limited physical hardware size.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of fractional time allocations in terms of improving the capacity of single-user and singleinput single output HD decode-and-forward systems has been shown earlier e.g. in [38], [39]. To sum up, we provide a brief comparison of the related literature in Table I.…”
Section: Bandwidth Allocation √mentioning
confidence: 99%